Peramalan Jumlah Permintaan Vaksin Meningitis di KKP Kelas I Surabaya (Menggunakan Metode Single Moving Average) - Dimas Syafi Aldi; Maki Zamzam (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Meningococcal meningitis is an acute inflammatory infection of the lining of the brain and spinal cord caused by the bacteria Neisseria meningitides. This disease can cause brain damage with a case fatality of 50% if not treated quickly. One effort to prevent the transmission of meningitis is to administer the meningococcal meningitis vaccine, which is an absolute requirement for all prospective Hajj and Umrah pilgrims. This research was conducted from September to December 2023 using secondary data, namely KKP Class I Surabaya annual report data for 2013-2022. The method used in this research is quantitative forecasting with the forecasting carried out is Simple Moving Average using RStudio software. The forecast results for meningitis vaccination demand for 2023-2026 using the 4-year SMA method are 31,768.50, this value is smaller than the 2013-2019 vaccine demand, the results of this forecast have an MSE value of 36,048,718.225. This result can still be tolerated and is used by the Surabaya Class I Port Health Office (KKP) to reduce the number of vaccines in stock so as not to stock too much meningitis vaccine.